The Innovativeness of the Economies of European Union Candidate Countries – an Assessment of Their Innovation Gap in Relation to the EU Average - Edyta Dworak (Comparative Economic Research, 2024)
Innovation is nowadays seen as an essential success factor in achieving economic prosperity and competing in markets. It is one of the most important determinants of the competitive process throughout the world, helping economies catch up with developing and changing technologies while revealing those countries’ innovation perspectives.